2015
DOI: 10.3389/fnbeh.2015.00251
|View full text |Cite
|
Sign up to set email alerts
|

Marmosets treated with oxytocin are more socially attractive to their long-term mate

Abstract: Adult male-female bonds are partly characterized by initiating and maintaining close proximity with a social partner, as well as engaging in high levels of affiliative and sociosexual behavior. Oxytocin (OXT), a neuromodulatory nonapeptide, plays a critical role in the facilitation of social bonding and prosocial behavior toward a social partner (Feldman, 2012). However, less attention has been given to whether augmentation of OXT levels in an individual alters others’ perceptions and behavior toward an OXT-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 74 publications
(98 reference statements)
2
43
0
Order By: Relevance
“…It is alternatively possible the our OT treatment did not produce a big effect because OT administered intranasally may not abundantly penetrate the brain; though large doses may have strong peripheral effects. While this study cannot speak directly to which central or peripheral mechanism OT modifies behaviour, previous studies using this intranasal OT procedure in marmosets have shown socially-specific effects of intranasal OT treatment across multiple social realms (Cavanaugh et al, 2015, 2014; Mustoe et al, 2015; Smith et al, 2010; Taylor & French, 2015). However, considerably more experimental research is needed in both human and animal populations, to establish whether and how administration of OXT reliably affects how individuals maintain cooperative relationships across a diversity of social interactions and species.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…It is alternatively possible the our OT treatment did not produce a big effect because OT administered intranasally may not abundantly penetrate the brain; though large doses may have strong peripheral effects. While this study cannot speak directly to which central or peripheral mechanism OT modifies behaviour, previous studies using this intranasal OT procedure in marmosets have shown socially-specific effects of intranasal OT treatment across multiple social realms (Cavanaugh et al, 2015, 2014; Mustoe et al, 2015; Smith et al, 2010; Taylor & French, 2015). However, considerably more experimental research is needed in both human and animal populations, to establish whether and how administration of OXT reliably affects how individuals maintain cooperative relationships across a diversity of social interactions and species.…”
Section: Discussionmentioning
confidence: 73%
“…For instance, treatment with Pro 8 -OXT, but not the consensus mammalian ligand (Leu 8 -OXT), reduced both sociosexual behaviour and prosocial food sharing toward opposite-sex strangers (Cavanaugh et al, 2014; Mustoe et al, 2015). Additionally, OXT enhances responsiveness to infant stimuli in male marmosets (Saito & Nakamura, 2011; Taylor & French, 2015), social attractiveness (Cavanaugh, Huffman, Harnisch, & French, 2015), and basal OXT levels are synchronized with levels of affiliative behaviour (Finkenwirth, van Schaik, Ziegler, & Burkart, 2015). These findings highlight how OXT shapes the maintenance of cooperative social relationships (male-female pair bonds; parental-offspring bonds) in marmosets by reducing interest in opposite-sex strangers and enhancing interest toward infant stimuli, two characteristics that may preserve biparental cooperative relationships.…”
Section: Introductionmentioning
confidence: 99%
“…Since marmosets display a similarly flexible pattern of sociosexual behavior as humans (Buss and Schmitt, 1993; Cavanaugh et al, 2015; Cavanaugh et al, 2014), continued research on the neurochemical basis of social attachment and recognition in marmosets (Cavanaugh et al, 2015; Cavanaugh et al, 2014; Mustoe et al, 2015; Smith et al, 2010), for example, provides direct comparisons to many analogous studies in rodents discussed earlier on this topic and offers the opportunity to identify shared and derived features of these core mammalian social behavioral systems in primates. Furthermore, marmoset active social signaling paradigms represent potential models for understanding the neural mechanisms underlying facets of language, in particular the intricate interplay between social communication and social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…IN OT also modified social behavior by altering the behavior of untreated partners toward their treated partner. Female marmosets initiated and maintained proximity more often when their mate was treated with IN OT compared to when their mate was treated with a saline control, suggesting that OT makes male marmosets more ‘socially attractive’ (Cavanaugh et al, 2015). Unlike the measure of partner preference in marmosets, however, this effect was ligand-specific: females modified behavior toward male partners similarly when males were treated with either Pro 8 -OT or Leu 8 -OT.…”
Section: Neuropeptide Diversity and Social Behavior In New World Mmentioning
confidence: 99%